Estrategias de habilidades cognitivas para el mejoramiento del aprendizaje de estudiantes con trastorno espectro autista en el tercero bachillerato “B” de la unidad educativa José María Velasco Ibarra - Peñarrieta Anchundia., Gabriela Liseth (2022)
The present research entitled Strategies and cognitive skills for the improvement of learning of students with autism spectrum disorder at the high school level of the educational unit José María Velasco Ibarra of Buena Fe Canton, The main objective of the research is to analyze strategies of cognitive skills for the improvement of learning of students with autism spectrum disorder at the high school level of the José María Velasco Ibarra Educational Unit of the Buena Fe Canton, during the school year 2020-2021, the research process has a critical prepositive approach that allowed gathering information and sustaining it through a statistical analysis, It is critical since a descriptive analysis of the phenomena to be investigated and prepositive, Given that its purpose is to analyze the strategies and cognitive skills to improve the learning of students, the data collection technique was the survey and for this purpose a questionnaire was applied to the teachers of the institution and a proposal was made with a training plan containing activities that allow the development in students with ASD to improve their concentration, memory and attention. The results of the validation allowed to know the importance of the application of this type of strategies within the educational unit, the requirement that teachers have in this important topic and the favorable application that will result in the students